Airway Relaxation Effects of Water-Soluble Sclerotial Extract From Lignosus rhinocerotis - Lee, Mei Kee; Li, Xiaojie; Yap, Alvin Chee Sum; Cheung, Peter Chi Keung; Tan, Chon Seng; Ng, Szu Ting; Roberts, Richard; Ting, Kang Nee; Fung, Shin Yee (Frontiers in Pharmacology, 2018)
Lignosus rhinocerotis has a long history of use by the indigenous community within East Asia to treat a range of health conditions including asthma and chronic cough. To date, there is limited scientific evidence to support its therapeutic effects in relieving these airways conditions. In this study, we examined the effects of the different molecular weight fractions [high-molecular-weight (HMW), medium-molecular-weight (MMW), and low-molecular-weight (LMW)] obtained from the cold water sclerotial extract (CWE) of L. rhinocerotis on airways patency using airway segments isolated from Sprague Dawley rat in an organ bath set-up. It is demonstrated that the HMW and MMW fractions exhibited higher efficacy in relaxing the pre-contracted airways when compared to the CWE and LMW fraction. In addition, the HMW fraction markedly supressed carbachol-, 5-hydroxytrptamine-, and calcium-induced airway contractions. CWE demonstrated a lower efficacy than the HMW fraction but it also significantly attenuated carbachol- and calcium-induced airway contractions. Results showed that the bronchorelaxation effect of CWE and fractions is mediated via blockade of extracellular Ca2+ influx. The composition analysis revealed the following parts of carbohydrate and proteins, respectively: HMW fraction: 71 and 4%; MMW fraction: 35 and 1%; and LMW fraction: 22 and 0.3%. Our results strongly suggest that the polysaccharide–protein complex or proteins found in the HMW and MMW fractions is likely to contribute to the bronchorelaxation effect of CWE.